Acceptor-donor-acceptor π-extended systems based on α-dithiophenetetrathiafulvalene (α-DT-TTF): Facile synthesis and photoconductivity studies. (August 2022) - Velho, Mariana F.G.; Paracana, Ana; Serra, João; Alcácer, Luís; Avó, João; Almeida, Manuel; Belo, Dulce; Alves, Helena; Charas, Ana
Abstract: π-Extended derivatives of the electron donor (D) α-dithiophenetetrathiafulvalene (α-DT-TTF) were prepared for the first time. The compounds consisting of α-DT-TTF covalently linked to N-alkylated phthalimides (Phth) or thieno[3, 4- c ]pyrrole-4, 6-dione (TPD), as the acceptors (A), in a A-D-A arrangements, were synthesized through microwave-assisted Stille cross-coupling reactions. DFT calculations reveal that the α-DT-TTF unit is coplanar with the TPD plane while a light twist occurs with the Phth end-unit, causing highly planar conjugated cores which are favorable for stacking and intermolecular charge transport. The A-D-A molecular design leads to red-shifted absorption spectra, in comparison with α-DT-TTF, and accessible reduction potentials, as indicated by electrochemical studies. Finally, photoconductivity in the UV–visible, up to 550 nm, was measured in crystals of one of the new compounds with the acceptor phthalimide. This work opens the way for the synthesis of new α-DT-TTF derivatives which can have applications in the optoelectronics field. Graphical abstract: We report a facile synthetic approach to prepare π-extended derivatives of α-DT-TTF which display tuned optical spectrum and photoconductivity. Image 1 Highlights: π-conjugated derivatives of the donor α-DT-TTF were synthesized. The compounds have A-D-A designs with phthalimide or TPD derivatives as acceptors. The synthesis involved microwave-assisted Stille cross-coupling reactions. The new compounds showed an additional red-shifted absorption band. Photoconductivity in the UV–Vis was measured in crystals of one of the derivatives.